Group A Streptococcus Induces LAPosomes via SLO/β1 Integrin/NOX2/ROS Pathway in Endothelial Cells That Are Ineffective in Bacterial Killing and Suppress Xenophagy - Yi-Lin Cheng (American Society for Microbiology, 2019)
ABSTRACT Group A streptococcus (GAS) is an important human pathogen which can cause fatal diseases after invasion into the bloodstream. Although antibiotics and immune surveillance are the main defenses against GAS infection, GAS utilizes internalization into cells as a major immune evasion strategy. Our previous findings revealed that light chain 3 (LC3)-associated single membrane GAS-containing vacuoles in endothelial cells are compromised for bacterial clearance due to insufficient acidification after fusion with lysosomes. However, the characteristics and the activation mechanisms of these LC3-positive compartments are still largely unknown. In the present study, we demonstrated that the LC3-positive GAS is surrounded by single membrane and colocalizes with NADPH oxidase 2 (NOX2) complex but without ULK1, which are characteristics of LC3-associated phagocytosis (LAP). Inhibition of NOX2 or reactive oxygen species (ROS) significantly reduces GAS multiplication and enhances autolysosome acidification in endothelial cells through converting LAP to conventional xenophagy, which is revealed by enhancement of ULK1 recruitment, attenuation of p70s6k phosphorylation, and formation of the isolation membrane. We also clarify that the inactivation of mTORC1, which is the initiation signal of autophagy, is inhibited by NOX2- and ROS-activated phosphatidylinositol 3-kinase (PI3K)/AKT and MEK/extracellular signal-regulated kinase (ERK) pathways. In addition, streptolysin O (SLO) of GAS is identified as a crucial inducer of ROS for β1 integrin-mediated LAP induction. After downregulation of β1 integrin, GAS multiplication is reduced, accompanied with LAP inhibition and xenophagy induction. These results demonstrate that GAS infection preferentially induces ineffective LAP to evade xenophagic killing in endothelial cells through the SLO/β1 integrin/NOX2/ROS pathway. IMPORTANCE Our previous reports showed that the LC3-associated GAS-containing single membrane vacuoles are inefficient for bacterial clearance in endothelial cells, which may result in bacteremia. However, the characteristics and the induction mechanisms of these LC3-positive vacuoles are still largely unknown. Here we provide the first evidence that these LC3-positive GAS-containing single membrane compartments appear to be LAPosomes, which are induced by NOX2 and ROS. Through NOX2- and ROS-mediated signaling, GAS preferentially induces LAP and inhibits bacteriostatic xenophagy in endothelial cells. We also provide the first demonstration that β1 integrin acts as the receptor for LAP induction through GAS-produced SLO stimulation in endothelial cells. Our findings reveal the underlying mechanisms of LAP induction and autophagy evasion for GAS multiplication in endothelial cells.